KNOWLEDGE GAP DAN ADAPTASI LINGKUNGAN KERJA KARYAWAN LOKAL DI HOTEL MILIK ASING - Soares, Janio Abilio Madeira; Prabawa, Titi Susilowati (Universitas Kristen Satya Wacana, 2017)
This research is meant to explore how local employees who work in International hotels in Dili, the capital city of Timor Leste adapt to the working environment. Without enough knowledge about hospitality, they acquire the skills through the knowledge transfer from the senior workers and through learning by doing. This research uses qualitative approach. In order to obtain data, in-depth interviews were done with 16 employees of the two hotels under research, i.e., Novo Turismo Hotel and Timor Plaza hotel. The research finds that kinship value in their working environment helps to accelerate transfer knowledge for the employees in Novo Turismo Hotel dan Timor Plaza. The process brings positive effects to training fund, potentials of internal conflicts and the cost of damages caused by the negligence of local employees.